Avoidable Ignorance and the Ethics of Risk in Child Welfare*. Issue 4 (2nd October 2017) - Gambrill, Eileen
Abstract : Sources of risk to children include far more than risk of harm to children from biological parents. Key opportunities to reveal and decrease avoidable ignorance that contribute to avoidable risk to children and families have been neglected such as clearly describing the evidentiary status of services provided and outcomes attained. A systemic view of risk requires attention to faulty assessment, referral to agencies that offer ineffective programs, failure to monitor outcomes and the quality of the social worker–client relationship on an ongoing basis, dysfunctional organizational arrangements and failure to involve clients as informed participants. An examination of the websites of child welfare agencies in the San Francisco Bay Area revealed that not one offered information that would enable informed decision making. Education programs may fail to help students to acquire skills in the process of evidence-informed practice. Based on a systemic view of risk, an agenda to decrease avoidable ignorance that contributes to avoidable risks to children and families is suggested emphasizing informed consent obligations. This includes increasing transparency regarding what is done to what effect including professional education and welcoming criticism of practices and policies and related claims. Reasons for failure to reveal and decrease such ignorance are explored including economic interests in the adoption and child welfare services industry.